Synthesis and Thermal Properties of Two Novel P-N Compounds - Wei, Shanshan; Chen, Ligong; Li, Yang (Asian Journal of Chemistry, 2015)
Two novel P-N compounds were synthesized through a two-step reaction including the synthesis of 2-chloro-5,5-dimethyl-1,3,2-dioxaphosphorinane-2-oxide (M) and its reaction with 2,2,6,6-tetramethylpiperidine-4-amine and N-butyl-2,2,6,6-tetramethylpiperidin-4-amine. The structures were confirmed by NMR (1H, 13C, 31P), FT-IR and MS. Their thermal properties were also evaluated by thermogravimetric analysis (TGA). The TG curves showed that the two compounds have residues of 4.9 and 1.1 wt % at 600 ºC and the temperature of maximum weight loss rate (Tmax) was 292 and 255 ºC, respectively.